1990
DOI: 10.1002/eji.1830201009
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin heavy chain variable region family usage is independent of tumor cell phenotype in human B lineage leukemias

Abstract: During B cell development, immunoglobulin heavy chain (IgH) variable region (VH) genes are rearranged and expressed in a programmed manner and accumulating evidence suggests recurrent utilization of developmentally restricted VH genes in malignant B lymphoid populations. We have used polymerase chain reaction gene amplification in conjunction with a panel of VH family-specific amplimers to directly compare the repertoire of VH region rearrangement in mature, CD5+ B cell chronic lymphocytic leukemia with that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(103 citation statements)
references
References 57 publications
6
96
1
Order By: Relevance
“…2). This mean value is significantly shorter than that previously reported for 51p1-expressing CLL B cells (19.08 Ϯ 3.5: p Ͻ 0.0001, n ϭ 36 unpaired t test) (6,7,14,(17)(18)(19)(20)(21), as well as shorter than these 36 sequences combined with 15 additional 51p1-expressing CLL sequences reported in the literature (18.80 Ϯ 3.2: p Ͻ 0.0001, n ϭ 51 unpaired t test) (6,7,14,(17)(18)(19)(20)(21)(22)(23)(24). The mean CDR3 length of the 39 sequences is also not significantly different from that calculated for the same and similar blood B cell samples using allele-specific PCR (Fig.…”
Section: Sequence Analysis Of 51p1 Expressed In Normal Blood B Cellscontrasting
confidence: 61%
See 1 more Smart Citation
“…2). This mean value is significantly shorter than that previously reported for 51p1-expressing CLL B cells (19.08 Ϯ 3.5: p Ͻ 0.0001, n ϭ 36 unpaired t test) (6,7,14,(17)(18)(19)(20)(21), as well as shorter than these 36 sequences combined with 15 additional 51p1-expressing CLL sequences reported in the literature (18.80 Ϯ 3.2: p Ͻ 0.0001, n ϭ 51 unpaired t test) (6,7,14,(17)(18)(19)(20)(21)(22)(23)(24). The mean CDR3 length of the 39 sequences is also not significantly different from that calculated for the same and similar blood B cell samples using allele-specific PCR (Fig.…”
Section: Sequence Analysis Of 51p1 Expressed In Normal Blood B Cellscontrasting
confidence: 61%
“…Allelespecific PCR of rearranged 51p1 genes from eight normal blood and tonsillar B cell samples revealed a mean CDR3 length that ranges from 14.6 to 15.5 codons. Both individually and collectively, the mean CDR3 lengths determined using either genomic DNA or cDNA from normal blood or tonsillar B cells were significantly different from the 18.8-codon (Ϯ3.2, n ϭ 51) mean CDR3 length noted for 51p1-encoded Ig expressed by CLL B cells ( p Ͻ 0.0001; see Table I) (6,7,14,(17)(18)(19)(20)(21)(22)(23)(24). However, the calculated mean CDR3 lengths of 51p1-encoded Ig of normal blood B cells were not significantly different from the mean CDR3 lengths of 146 Ig encoded by random V H genes expressed by normal adult B cells (13.9 Ϯ 4.2) (25,26) or the mean CDR3 lengths of CLL B cells that express IgH encoded by V H 1 genes other than 51p1 (7,14,20,22,23).…”
Section: Discussionmentioning
confidence: 91%
“…We then tested the effects of Atiprimod on the IL-6-responsive myeloma cell line MM-1 (Deane and Norton, 1990). As expected, we found that IL-6 induced STAT3 phosphorylation in a dosedependent manner at concentrations ranging from 0.5 to 2 ng ml À1 .…”
Section: Atiprimod Downregulates Both Il-6-induced and Constitutive Ssupporting
confidence: 53%
“…To avoid contamination by residual effete myeloma cells, only isolated colonies were microaspirated. The rearranged IgH gene in the DNA from the diagnostic myeloma BM cells and from individual colonies was amplified using a modification of a previously described method (Deane and Norton, 1990). Briefly, cells were placed in 1 ml of QuickExtract DNA Extraction solution 1.0 (Epicentre, Madison, WI, USA) and lysed in accordance with the manufacturer's protocol.…”
Section: Clonogenic Assaymentioning
confidence: 99%
“…At diagnosis, we identified IgH gene rearrangements using the consensus V-region primers FR-1C 26 or FR-2B, 27 in conjunction with a universal J H primer. 28 Reaction mixtures of 50 ml contained 1 Â PCR buffer (PE Applied Biosystems, Foster City, CA, USA), 50-200 ng of genomic DNA, 1.5-2.5 mM MgCl 2 , 200 mM dNTPs, 0.25-0.50 mM primers, and 1 U of AmpliTaq Gold (PE Applied Biosystems). PCR products were analyzed on 3% agarose gels and potential rearrangements were analyzed by heteroduplex analysis on 6% acrylamide -1 Â TBE gels.…”
Section: Pcr Amplification Of Immunoglobulin Genesmentioning
confidence: 99%